2015
DOI: 10.1103/physrevb.92.214408
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear domain wall resonance in garnet films with perpendicular anisotropy: Critical role of nonlinear damping

Abstract: International audienceDomain wall resonance spectra in the weakly nonlinear regime for garnet films with a perpendicular anisotropy supporting parallel stripe domains have been investigated using micromagnetic simulations and zero-field broadband ferromagnetic resonance experiments. The main characteristics of the 2D numerical micromagnetic approach we developed is to solve the Landau-Lifshitz equation by an iterative method in the frequency domain and to incorporate a nonlinear phenomenological damping term. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…For P=200 mW, the resonance linewidth is enhanced by a factor 1.8 with respect to the linear regime. Such power evolutions have been previously reported and nicely reproduced by micromagnetic simulations including a nonlinear damping parameter [9] for a sample with similar magnetic parameters except a sligthly larger value of the saturation magnetization. (iii) The power absorption at resonance first increases rapidly with P and then saturates at P s = 50 mW (Fig.…”
Section: Fundamental Dw Resonancessupporting
confidence: 76%
See 2 more Smart Citations
“…For P=200 mW, the resonance linewidth is enhanced by a factor 1.8 with respect to the linear regime. Such power evolutions have been previously reported and nicely reproduced by micromagnetic simulations including a nonlinear damping parameter [9] for a sample with similar magnetic parameters except a sligthly larger value of the saturation magnetization. (iii) The power absorption at resonance first increases rapidly with P and then saturates at P s = 50 mW (Fig.…”
Section: Fundamental Dw Resonancessupporting
confidence: 76%
“…These effects have been experimentally observed both for the domain mode resonances [7] and for the lowest-frequency DW mode resonance [8,9]. In addition, it has been recently shown that a correct description of the power dependences of the resonance shift and the line broadening in a phenomenological approach requires to take into account a nonlinear damping parameter [7,9]. Further increasing the amplitude of the pumping field results in a possible parametric excitation of DW waves with k 0 through a three-DW-wave interaction mechanism (equivalent to the first-order Suhl instability for the ferromagnetic resonance (FMR) [10]) or a four-DW-wave interaction process (second-order Suhl instability for the FMR [10]) as theoretically analyzed [11] and revealed using a magneto-optic detection [12].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation